(3eLed GddZIs - (3GHf aGQS , CHh GdMSjf CMeO Hf aGQS Hf RcQjGA GdbRhjfj GdQGRj,J (B395 (3g` s ((3CHh HcQ eMeO Hf eMSf GdNhdi s)
(3ChdgG (B:s
(3HGH GdVGO heG HYOgG ai GdeVGYa hGdeWGHb (B: (3hGdVYVYI GdNVhY hGdJPdd bGd GdNdjd GdYLjR GdQbjb s
(3GdLRA GdKGfi hgh GdfUa GdKGfi ef GdcJGHs
(3HChdgG Jedc eDQN SfI (B546 (3g`s
(3fSNI JGSYI JJab ai BNQgG eY BNQ fSNI (B[ (3GdeJMa GdYQGbi (B_ (3HZOGO (B542 ] (3HGNJdGa ai HYV GdLed hGdYHGQGJ hGdeaQOGJs
(3fSNI ebGHdI heUMMIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
Keywords: (3GddZIs